Sisko Hybrid Nanofluid Model for Blood Flow Over an Exponentially Stretched Cylinder Incorporating Homogeneous–Heterogeneous Reactions: A Framework of the Modified Buongiorno Model - V. Karthik; P. Asaigeethan; A. Varsha Vincy; B. Thrisha; Selvakumar Periyasamy (International Journal of Chemical Engineering)
This study comprehensively investigates hemodynamic flow behavior in a blocked-up, tapered arterial passage using the Sisko hybrid nanofluid model, incorporating both homogeneous and heterogeneous reactions. Extending the modified Buongiorno model, we explored the effects of nanoparticle interaction and non-Newtonian fluid characteristics n<1 and n>1 on hemodynamics. The geometry of the exponentially stretched cylinder is considered to analyze realistic flow conditions, and mathematical modeling is employed to derive governing equations for flow behavior. The results reveal significant alterations in flow velocity, shear stress along the vessel wall, and temperature distribution due to the presence of nanoparticles and the stenosis structure. Numerical simulations indicate that incorporating nanoparticles improves the blood’s thermal and flow characteristics, enhancing perfusion. This work contributes to understanding complex blood flow dynamics in stenotic conditions and offers insights into potential therapeutic applications for vascular diseases.